Speaking effectively to one or one thousand - Dexter, Denise; Silberg, Bob; CRM Learning (California : CRM Films, 1992)
Describes ten key communication skills and techniques for effective, interpersonal communication, and attempts to link public speaking to everyday interpersonal communication
Title from title screen
Based on the material developed by Decker Communications, Christopher hegarty and Toastmaster, Int.
Executive producer, Peter J. Jordan ; editor, Jill Nemiro
Hosted by Steve Landesberg
Keywords: Public speaking; Communication skills; Word choice and usage